Muassasah Dâr al-Salâm Gontor wa Dauruhâ fî T a’lîm al-ghah al-’Arabiyah li-al-Nâtiqîn bi Ghairihâ bi Ma’ad Gontor Namudhajan - Dihyatun Masqon (Universitas Darussalam Gontor, 2014)
Beyond the shadow of any doubt, Islam is considered as key factor for the spreading of Arabic language all over the world. That is because of its close association with Islam, not to mention its vital role as only tool to understand the book of Islam, namely al-Qur’an. When Islam entered Indonesian archipelago, Arabic then made its way into parts of these islands and influenced a lot the language of the people known as Bahasa Indonesia. Moreover, the teaching of Arabic from that very early time took place in order to just understand and gain ability to read certain Arabic books, mainly in the field of Islamic and Arabic sciences. With the raising of the down of the twentieth century, corresponding to the 14th H, which is known in Muslim world as the age of renaissance, the teaching of Arabic took new approaches with a specific method for reforming the teaching of language skills. In this regard, Darussalam Gontor Institution, founded in 1926, took leading role in this area using modern method which enable students to understand, speak, read, and write Arabic with native speech. The motto used in this institution is: The method is more important than the material. The teacher is more important than the method. But the spirit of the teacher is the most important. Obviously the researcher found that linguistic education in Gontor focused to give the students the ability to communicate correctly and clearly, both orally or in writing. Linguistic communication should be directed the development of the four language skills simultaneously. Another factors contributed to the success of Gontor in teaching Arabic for non-native speakers are: the availability of effective positive linguistic environment, and the use of Arabic and English as well as medium of teaching and expressing.